An Investigation Of Traffic Induced Vibration Effect On Structure And Human Sensitivity - Ong, Khang Yoong (Universiti Sains Malaysia, 2006)
Vibrations caused by industrial activities such as piling, rock blasting, traffic, and vibrating machinery result as annoyance to human beings and generate possible structural damages. Therefore, vibration monitoring and analysis are required to predict the effects of the vibrations. In this project, measurement of the traffic-induced vibrations has been carried out by using the μMX system. The effects of traffic vibration have been evaluated by using some standard structural damaging figures and tables. Several factors might have contributed to traffic vibration levels, such as road condition, vehicle speed, vehicle weight, soil conditions, vehicle suspension system, and distance between the structure and the road. The characteristics of the traffic vibration in terms of the vehicle weight and distance to road center were discussed. For the first study, vibrations data were collected on different categories of vehicle. The results proved that the heavier the vehicle, the vibration level will be increased. For the second study, truck vibration data were collected with varying distances from the source. Then, the results were compared with the data of train motion induced vibration. The results showed that the trend of the peak velocity distribution graph for truck vehicle was similar with train motion vibration, even though the delivered energy between them was different. The results of this project can be used as a guide in predicting the effects of the traffic induced vibration to the nearby buildings and human beings.